Indonesia Financial Sector Assessment Program : Insurance Core Principles - International Monetary Fund (World Bank, Washington, DC, 2018)
This assessment of insurance regulation in Indonesia was carried out as part of the 2016-17 Financial Sector Assessment Program (FSAP). The Indonesian insurance sector is still vulnerable to a number of material risks. A number of insurers have failed in the last 10 years. After its establishment, OJK has taken prompt action in order to reduce the loss to policyholders by taking strong actions against four insurers with material deficits. OJK has monitored the capital adequacy of insurers through its risk based supervision scheme. During the recent market turmoil in 2015, the solvency requirement was relaxed for nine months while introducing the temporary suspension of mark to market valuation rules. The Indonesian insurance industry is exposed to significant catastrophic risk with domestic concentrations through mandatory reinsurance programs. The low interest rate environment in advanced economies is also affecting the life insurance sector, as insurers have some underwriting denominated in USD.